Relationship between Self-Regulated Learning and Academic Performance among Secondary School Students - Maqsoom, Syeda; Atta, Saman; Bibi, Ruqia (ACADEMIA International Journal for Social Sciences, 2026)
This study investigates the relationship between self-regulated learning and academic performance among secondary school students. The purpose of the research was to examine how students’ ability to regulate their own learning processes influences their academic achievement in school settings. Self-regulated learning is a multidimensional construct that involves planning, monitoring, and evaluating one’s learning activities, while academic performance refers to students’ achievement levels as reflected in their academic results. The study was conducted on a sample of 300 secondary school students selected through stratified random sampling from District Rawalpindi. A quantitative correlational research design was used, and data were collected through a structured questionnaire based on a Likert scale along with academic records. Pearson correlation coefficient was applied to analyze the relationship between the variables. The findings of the study revealed a moderate positive and statistically significant relationship between self-regulated learning and academic performance (r = .566, p < .01). This indicates that students who demonstrate higher levels of self-regulated learning tend to achieve better academic results. The results further suggest that self-regulated learning plays an important role in enhancing students’ academic success by improving their ability to manage time, set goals, and apply effective learning strategies. The study concludes that strengthening self-regulated learning skills can significantly contribute to improving academic performance among secondary school students. On the basis of the findings, it is recommended that teachers should integrate self-regulated learning strategies into classroom practices to enhance students’ academic outcomes. Educational institutions should provide training and awareness programs to develop self-regulation skills among students. Curriculum developers should also include activities that promote independent learning and self-monitoring. The study highlights the importance of fostering self-regulated learning in secondary education to improve overall academic achievement.